Causal Loop Diagram Model of the Owner's Critical Role in the Success of Port Infrastructure Design-Build Projects - Budiman Nugraha Herdian; Tri Joko Wahyu Adi (Publikasi Indonesia, 2024)
The complexity and dynamics of Design-Build projects require stakeholders in the Construction Industry to better understand each party's roles and responsibilities to achieve success. The criterion of project success and the factors affecting it is a dynamic mutual relationship. This study proposes a causal loop diagram model to provide an overview of the influence of the Owner's role in achieving the Port Infrastructure Design-Build project's cost, time and quality success. Research variables were obtained through in-depth literature studies and interviews with project owners and project practitioners experienced in design-build projects.